The Interconnected Mechanisms of Oxidative Stress and Neuroinflammation in Epilepsy - Anna L. M. Parsons; Eboni M. V. Bucknor; Enrico Castroflorio; Tânia R. Soares; Peter L. Oliver; Daniel Rial (Antioxidants, 2022)
One of the most important characteristics of the brain compared to other organs is its elevated metabolic demand. Consequently, neurons consume high quantities of oxygen, generating significant amounts of reactive oxygen species (ROS) as a by-product. These potentially toxic molecules cause oxidative stress (OS) and are associated with many disorders of the nervous system, where pathological processes such as aberrant protein oxidation can ultimately lead to cellular dysfunction and death. Epilepsy, characterized by a long-term predisposition to epileptic seizures, is one of the most common of the neurological disorders associated with OS. Evidence shows that increased neuronal excitability—the hallmark of epilepsy—is accompanied by neuroinflammation and an excessive production of ROS; together, these factors are likely key features of seizure initiation and propagation. This review discusses the role of OS in epilepsy, its connection to neuroinflammation and the impact on synaptic function. Considering that the pharmacological treatment options for epilepsy are limited by the heterogeneity of these disorders, we also introduce the latest advances in anti-epileptic drugs (AEDs) and how they interact with OS. We conclude that OS is intertwined with numerous physiological and molecular mechanisms in epilepsy, although a causal relationship is yet to be established.